Digital Platforms and Tamil Film Industry: The New Business Horizons - V, Prabakaran (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Distributing films is that the ending of the film creating that follows Pre-production, production and then post-production of the moving picture. There are many necessary stages before distribution of the moving picture. It’s a method within which moving picture is made available to the audiences to look at it. Skilled film distributors perform this task. Movies often play at theaters that are owned by the studio or the parent company of the studio that makes the film, thereby ensuring release and the return of profit into their entities. In a way, it’s almost guaranteeing a return on investment. The average filmgoers growing affinity to digital platforms is making the trade to rethink older paradigms of entertainment consumption and revenue making across varied verticals like music, films, television, and live entertainment. This paper looks at the new trends in the film industry in the digital platforms of money making. How to cite this article: Prabakaran V. Digital Platforms and Tamil Film Industry: The New Business Horizons. J Adv Res Jour Mass Comm 2018; 5(4): 101-103. DOI: https://doi.org/10.24321/2395.3810.201837